Theoretical insights into surface-phase transition and ion competition during alkali ion intercalation on the Cu4Se4 nanosheet - Yu, Yang-Xin (Physical chemistry chemical physics : PCCP, 2023)
The development of stable and efficient electrode materials is imperative and also indispensable for further commercialization of sodium/potassium-ion batteries (SIBs/PIBs) and new detrimental issues such as proton intercalation arise when utilizing aqueous electrolytes. Herein the electrochemical performance of the Cu4Se4 nanosheet was determined for both organic and aqueous SIBs and PIBs. By means of density functional theory calculation, Na+, K+ and H+ intercalations onto both sides of the Cu4Se4 nanosheet were revealed. The Cu4Se4 nanosheet well maintains its metallic electronic conductivity and the changes in lateral lattice parameters are within 4.66% during the whole Na+/K+ intercalation process for both SIBS and PIBs. The theoretical maximum Na/K storage capacity of 188.07 mA h g−1 can be achieved by stabilized second-layer adsorption of Na+/K+. The migration barriers of Na and K atoms on the Cu4Se4 nanosheet are 0.270 and 0.173 eV, respectively. It was discovered that Na/K- intercalation in the first layer is accompanied by a first-order surface phase transition, resulting in an intercalation voltage plateau of 0.659/0.756 V, respectively. The region of the two-surface phase coexistence for PIBs, is shifted toward a lower coverage when compared with that for SIBs. The partially protonated Cu4Se4 nanosheet (HxCu4Se4, x ≤ 10/9) was revealed to be structurally and thermodynamically stable. While the partially protonated Cu4Se4 nanosheet is favorable in acidic electrolytes (pH = 0) when protons and Na/K ions compete, we showed that Na+/K+ intercalated products may be preferred over H+ at low coverages in alkali electrolyte (pH = 14). However, the proton intercalation substantially decreases the battery capacity in aqueous SIBs and PIBs. Our work not only identifies the promising performance of Cu4Se4 nanosheets as an electrode material of SIBs and PIBs, but also provides a computational method for aqueous metal-ion batteries.